Expression of Drosophila Ten-a, a dimeric receptor during embryonic development. - Fascetti, N.; Baumgartner, S. (Mechanisms of Development, 2002)
Ten-a and Ten-m are the two Drosophila members of the newly discovered Ten-m family of dimeric type II transmembrane proteins. Here, we report complete cDNA cloning and protein expression patterns of Ten-a. The Ten-a protein, a dimeric receptor of about 500 kDa is mainly expressed on axons of the embryonic central nervous system and on muscle attachment sites.